2016
DOI: 10.1038/srep19173
|View full text |Cite
|
Sign up to set email alerts
|

Combined Labelled and Label-free SERS Probes for Triplex Three-dimensional Cellular Imaging

Abstract: Cells are complex chemical systems, where the molecular composition at different cellular locations and specific intracellular chemical interactions determine the biological function. An in-situ nondestructive characterization of the complicated chemical processes (like e.g. apoptosis) is the goal of our study. Here, we present the results of simultaneous and three-dimensional imaging of double organelles (nucleus and membrane) in single HeLa cells by means of either labelled or label-free surface-enhanced Ram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 45 publications
0
55
0
2
Order By: Relevance
“…[197] By using Ag nanotriangles modified with aRaman reporter and folic acid, the SERS tags bound to the folate receptors of ahuman ovary cancer cell line,a nd the uptake of the nanoparticles was investigated by dark-field microscopy and SERS. [203] This enabled the 3D multilabel cell imaging of single HeLa cells,r endering this approach attractive for biomedical investigations on the subcellular level. [199] As anew Raman reporter, graphene oxide was used to modify AgNPs.…”
Section: Specific Sers Labelsmentioning
confidence: 99%
“…[197] By using Ag nanotriangles modified with aRaman reporter and folic acid, the SERS tags bound to the folate receptors of ahuman ovary cancer cell line,a nd the uptake of the nanoparticles was investigated by dark-field microscopy and SERS. [203] This enabled the 3D multilabel cell imaging of single HeLa cells,r endering this approach attractive for biomedical investigations on the subcellular level. [199] As anew Raman reporter, graphene oxide was used to modify AgNPs.…”
Section: Specific Sers Labelsmentioning
confidence: 99%
“…Further studies also showed that AuNP SERS particle tracking in cytosol was able to correlate dynamic Raman features to particle motion [316]. Combined label/label-free nanoprobes were also recently used for 3D imaging [317]. Pavillon et al have also developed automated feature-based SERS spectra recognition in cells [318].…”
Section: Applicationsmentioning
confidence: 99%
“…The results show that rich vibrational information is observed in the range of 400–1,800 cm −1 , from the contributions of all kinds of biomacromolecules in cells such as proteins, amino acids, nucleic acids, and carbohydrates . Characteristic peaks of MCF‐7 cells compared with HepG2 cells are highlighted in Figure , for example, 818, 926, and 1,241 cm −1 from protein, contributed to tyrosine, C─C stretching, and amide III, respectively.…”
Section: Resultsmentioning
confidence: 99%